2021
DOI: 10.1007/s42990-021-00054-9
|View full text |Cite
|
Sign up to set email alerts
|

New trenching results along the İznik segment of the central strand of the North Anatolian Fault (Turkey): an integration with preexisting data

Abstract: This paper provides a new contribution to the construction of the complex and fragmentary mosaic of the Late Holocene earthquakes history of the İznik segment of the central strand of the North Anatolian Fault (CNAF) in Turkey. The CNAF clearly displays lower dextral slip rates with respect to the northern strand however, surface rupturing and large damaging earthquakes (M > 7) occurred in the past, leaving clear signatures in the built and natural environments. The association of these historical events to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…On the same segment, Civico et al. (2021) opened two trenches and evidenced one mid‐19th century event, one penultimate event after the late seventh century and two older events before the mid‐fifth century CE. West of Iznik Lake, Ikeda, et al.…”
Section: Previous Slip Rates and Paleoseismological Studies On The Mnafmentioning
confidence: 99%
See 2 more Smart Citations
“…On the same segment, Civico et al. (2021) opened two trenches and evidenced one mid‐19th century event, one penultimate event after the late seventh century and two older events before the mid‐fifth century CE. West of Iznik Lake, Ikeda, et al.…”
Section: Previous Slip Rates and Paleoseismological Studies On The Mnafmentioning
confidence: 99%
“…South of the lake, Erginal et al (2021) reported a 50 cm high coseismic scarplet in beachrock deposits that they attributed to an eighth century rupture. On the same segment, Civico et al (2021) opened two trenches and evidenced one mid-19th century event, one penultimate event after the late seventh century and two older events before the mid-fifth century CE. West of Iznik Lake, Ikeda, et al (1989) proposed a mid-19th century event from archaeological remains found in a natural fault exposure.…”
Section: Previous Slip Rates and Paleoseismological Studies On The Mnafmentioning
confidence: 99%
See 1 more Smart Citation
“…To estimate this length, we rely on the magnitude estimated by historical seismology studies (see Table S1 in Supporting Information), from which a surface rupture length was derived using the relationship of Wells and Coppersmith (1984). The length of the vertical boxes corresponds to the dating of the events within 2σ uncertainty (Civico et al, 2021;Dikbas et al, 2018;Dogan, 2010;Gastineau et al, 2021;Ikeda, Suzuki et al, 1991;Klinger et al, 2003;Özalp et al, 2013;Rockwell et al, 2009; see Table S2 in Supporting Information for detailed data).…”
Section: Accepted Articlementioning
confidence: 99%
“…South of the lake, Erginal et al (2021) reported a 50 cm high coseismic scarplet in beachrock deposits that they attributed to an 8 th century rupture. On the same segment, Civico et al (2021) opened two trenches and evidenced one mid-19 th century event, one penultimate event after the late 7 th century and two older events before the mid-5 th century CE. West of Iznik Lake, Ikeda et al (1989) proposed a mid-19 th century event from archaeological remains found in a natural fault exposure.…”
Section: Confidential Manuscript Submitted To Tectonicsmentioning
confidence: 99%